Monetary policy in Poland: How the financial crisis changed the central bank's preferences - Joanna Mackiewicz-Łyziak (e-Finanse: Financial Internet Quarterly, 2017)
The aim of the study is to analyze the preferences of the Polish central bank concerning inflation and output gap stabilization and verification, and whether these preferences changed after the beginning of the global financial crisis. For this purpose Taylor rules are estimated by the means of GMM (linear Taylor rule) and LS with breakpoints (nonlinear Taylor rule) estimation methods. We find that the smoothing parameter decreased, the weight of the output gap increased and the weight of inflation decreased after the outburst of the crisis. Moreover, we calculate ex-post interest rate simulations to compare the actual interest rates set by the NBP with a hypothetical situation of no change in the central bank's preferences. The results suggest that the interest rates set by the NBP were significantly lower in comparison with the no-change scenario, in particular in the first quarters after the beginning of the crisis.
Keywords: E52; E58; C54; 330; monetary policy; linear and nonlinear Taylor rule; interest rates simulations; financial crisis